2011
DOI: 10.1007/s00586-011-1908-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver reliability assessment of computed tomographic 3D measurement of pedicles in scoliosis and size matching with pedicle screws

Abstract: Background In patients with scoliosis, the morphology of the pedicles differs from those in normal spines. Preoperative three-dimensional information of these complex anatomic situations means a great advantage for the surgeon in order to assess which pedicles can be instrumented safely avoiding screw misplacement and for the decisions in choosing the appropriate screw size. The objective of this study was to measure pedicle dimensions in scoliotic spines on three-dimensional computed tomographic (CT) scans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Krag et al [14] and Misenhimer et al [24] reported good correlation between CT-based and true morphometric measurements of pedicles in cadavers. Gstoettner et al [7] found substantial intra-and interobserver reliability of CT scans. However, to the best of our knowledge, numerous studies investigating morphologic features of the pedicle only focused on comparison between the concave and convex sides of scoliosis, which provides limited information regarding the deformed spine [2-4, 11, 15, 31, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Krag et al [14] and Misenhimer et al [24] reported good correlation between CT-based and true morphometric measurements of pedicles in cadavers. Gstoettner et al [7] found substantial intra-and interobserver reliability of CT scans. However, to the best of our knowledge, numerous studies investigating morphologic features of the pedicle only focused on comparison between the concave and convex sides of scoliosis, which provides limited information regarding the deformed spine [2-4, 11, 15, 31, 35].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that screw sizes available from the major manufacturers are limited, typically in 0.5 mm increments. Two studies in the current review specifically noted the inadequacy of current pedicle screw systems for instrumenting the midthoracic levels, with Liau et al 34 commenting that current systems are not suitable for the majority of the Malay population, and Gstoettner et al 36 concluding that one-third of midthoracic pedicles of scoliosis patients cannot be instrumented safely.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, when these studies are grouped by the age of their relevant patient population, only those dealing at least in part with a pediatric population offered recommendations for SD wider than the pedicle. 24,36,37 These studies, based on both insertion techniques, define the upper limits for pediatric SD/PW between 1.15 and 1.25.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New protocols have allowed for postacquisition generation of 3D surface reconstructions, which provide virtual 3D anatomic structures. Studies utilizing 3D reconstruction of 2D CT imaging data are promising, and the utility of this imaging technology has been demonstrated in the diagnosis of rotational and shear vertebral fractures, 6 assessment of congenitally abnormal pedicles, 7 and also establishment of safe entry points for pedicle screws in corrective scoliosis surgeries. 8 …”
Section: Introductionmentioning
confidence: 99%